Legalizing the Physical Fitness Test Battery for Employees of the Babylon Governorate Police Directorate and Installations - Safaa Kadhim Jawad Khafaji; Rawaa Allawi Kadhim; Raad Abdulameer Fenjan (Indian Journal of Forensic Medicine & Toxicology, 2021)
As for the research problem: There is a weakness in the physical fitness of the employees of the BabylonGovernorate Police Department, which may create loopholes that prevent the achievement of the tasksand duties assigned to the employee of the police in pursuing wanted persons or raiding or confrontingterrorists, and in light of the above, the researchers sought that the problem of the current study will answeron the following question: (What are the levels of physical fitness among employees of the BabylonGovernorate Police Directorate and installations)?. Among the objectives of the research are: preparing andstandardizing the physical fitness test battery for employees of the Babil Police Directorate and facilities,and getting acquainted with the special physical fitness of the employees of the Babylon Police Directorateand installations. The researchers used the descriptive method in the survey method for its suitability tothe nature of work, and it represented the community of employees of the Babylon Governorate PoliceDepartment and the establishments included in the course of those eligible for promotion, the July schedulefor the year (2021), and the research sample consisted of (142) affiliates, and they formed a percentage of(28.4%) of The research community, and they were chosen by a simple random method (lottery).